Risk of chemotherapy-induced febrile neutropenia with same-day versus next-day pegfilgrastim prophylaxis among patients aged ≥65 years: a retrospective evaluation using Medicare claims. (2nd September 2018) - Weycker, Derek; Hanau, Ahuva; Lonshteyn, Alexander; Bowers, Charles; Bensink, Mark; Garawin, Tamer; Chandler, David
Abstract: Background: Two recent evaluations reported that risk of febrile neutropenia (FN) may be higher when pegfilgrastim prophylaxis (PP) is administered on same day as chemotherapy rather than per recommendation (1–3 days following chemotherapy). Such evidence is based largely on the experience of younger privately insured adults and may not be generalizable to older patients in US clinical practice. Methods: A retrospective cohort design and data from Medicare Claims Research Identifiable Files (January 2008–September 2015) were employed. Patients were aged ≥65 years, had breast cancer or non-Hodgkin's lymphoma, received chemotherapy with intermediate/high risk for FN, and received PP in ≥1 cycle; cycles with PP were stratified based on administration day (same-day ["Day 0"] vs. 1–3 days following chemotherapy ["Days 1–3"]) and were pooled for analyses. Adjusted odds ratios (ORs) for FN during the cycle were estimated for patients who received PP on Day 0 versus Days 1–3. Results: Study population included 65, 003 patients who received PP in 261, 184 cycles; in 5% of cycles, patients received PP on Day 0. Incidence proportion for FN in cycle 1 was 11.4% for Day 0 versus 8.4% for Days 1–3; adjusted OR was 1.4 ( p < .001). Incidence proportion for FN when considering all cycles was 7.7% for Day 0 and 6.0% for Days 1–3; adjusted OR was 1.3 ( p < .001). Adjusted ORs when considering all cycles and only inpatient FN episodes (1.3, p < .001) and the narrow definition for FN (1.5, p < .001) were similar. Conclusions: Among Medicare patients receiving chemotherapy and PP in US clinical practice, PP was administered before the recommended timing in 5% of cycles and FN incidence was significantly higher in these cycles. Along with prior research, study findings support recently updated US practice guidelines indicating that PP should be administered the day after chemotherapy.